BETWEEN BIOETHICS AND TRANSHUMANISM: REMARKABLE PERSPECTIVES AND ACUTE CHALLENGES IN TRANSIT TO A POSSIBLE DYSTOPIAN FUTURE - VALENZUELA FERNÁNDEZ, ALEX (2023)
“Transhumanism, nowadays, is being incorporated into mass culture due to the fact that an increasing number of scientists are beginning to take very seriously the wide range of possibilities it comprises. The aim of this paper is to present an analysis of the problems and dilemmas faced by bioethics and its aspects in relation to transhumanism, showing the ideas in which convergence and divergence can be seen with respect to achievements and perspectives. It also shows the analysis of the current trends from different perspectives (social, legal, technological, moral, philosophical) in which transhumanism has been positioning itself and generating new panoramas. In the same direction, an aspect derived from such development is presented: neuderlaw, regarding the scope, perspectives and contradictions resulting from the development of neurosciences and their application in the legal field.“